The Differential Improvement Effects of the Strategy Map and Scorecard Perspectives on Managers' Strategic Judgments - Cheng, Mandy M.; Humphreys, Kerry A. (The Accounting Review, 2012)
ABSTRACT This study examines the effect that two key balanced scorecard (BSC) framework elements—causal linkages between strategic objectives in the strategy map and performance measures categorized by scorecard perspective—have on managers' ability to interpret the strategic relevance of external information and use this information to evaluate the appropriateness of an organization's strategy. We conduct two experiments, finding that presenting a set of strategic objectives as a strategy map enhances both managers' information relevance and strategy appropriateness judgments. We attribute this improvement to the explication of causal linkages between objectives in a strategy map. In contrast, presenting performance measures categorized by scorecard perspective only improves managers' strategy appropriateness judgments when the managers are provided with a set of strategic objectives that are not presented in a strategy map structure. Our study contributes to the literature by demonstrating that these two elements of the BSC framework have differential decision-facilitating impacts on managers' strategic judgments. Data Availability: Data are available from the authors upon request.